Changing narratives of youth crime from social causes to threats to the social - Dollinger, Bernd 1973- (Routledge, Taylor & Francis Group, 2020)
"Utilizing detailed narrative analyses, this book explores how narratives of youth crime have changed in recent decades"--
Keywords: Geschichte 1945-2019; Gesellschaftsbild; Jugendlicher Täter; Jugendkriminalität; Juvenile delinquency; Juvenile justice, Administration of